2017
DOI: 10.1177/1075547017696166
|View full text |Cite
|
Sign up to set email alerts
|

Thirty Years of a Science Communication Course in Australia

Abstract: Since 1985, the Science Circus program has recruited science graduates Australia-wide and provided them with science communication training leading to a university degree. On qualifying these graduates demonstrate highly diverse career paths reflecting the relevance of science communication training to other disciplines. Graduates, by their activities, have contributed to the growth of science communication as an academic discipline and an “industry”—both in Australia and abroad. It suggests that science commu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 15 publications
2
6
0
1
Order By: Relevance
“…Vidare spenner dei pedagogiske strategiane frå reine førelesingsseriar til praksisopphald i eksterne redaksjonar. Nokre undervisarar integrerer forskingsformidling som ein del av dei obligatoriske fagemna (Jaidev & Chan, 2018;Johnson et al, 2015;Reynolds et al, 2012), medan andre institusjonar tilbyr eigne emner eller studieprogram for forskingsformidling og vitskapsjournalistikk (McKinnon & Bryant, 2017;Mellor, 2013). Mange medieaktørar tilbyr også frittståande kurs der forskarar får trene på å handtere journalistar eller underhalde publikum frå ei scene.…”
Section: Undervisning I Forskingsformidlingunclassified
“…Vidare spenner dei pedagogiske strategiane frå reine førelesingsseriar til praksisopphald i eksterne redaksjonar. Nokre undervisarar integrerer forskingsformidling som ein del av dei obligatoriske fagemna (Jaidev & Chan, 2018;Johnson et al, 2015;Reynolds et al, 2012), medan andre institusjonar tilbyr eigne emner eller studieprogram for forskingsformidling og vitskapsjournalistikk (McKinnon & Bryant, 2017;Mellor, 2013). Mange medieaktørar tilbyr også frittståande kurs der forskarar får trene på å handtere journalistar eller underhalde publikum frå ei scene.…”
Section: Undervisning I Forskingsformidlingunclassified
“…This changed in January 2009 when the joint MSc degree program in science communication was introduced by the National University of Singapore (NUS) in collaboration with the Centre for the Public Awareness of Science (CPAS) at The Australian National University (ANU) (NUS FoS, 2018b). CPAS was responsible for developing one of the first specialised degree programs for science communication in 1987 (McKinnon and Bryant, 2017). Leveraging this expertise and combining the unique and complementary strengths of both ANU and NUS, the program at NUS targets both educators who wish to upgrade their skills in education as well as those working in areas of science policy, journalism and scientific writing.…”
Section: Nurturing Science Communicatorsmentioning
confidence: 99%
“…But this is increasingly turned into an unqualified assertion that science communication is a profession [e.g. Sánchez-Mora et al, 2015;McKinnon and Bryant, 2017;Gascoigne and Metcalfe, 2017]. On the other hand, the opposite has been put forward in a discussion of "informal science learning" [Matterson and Holman, 2012] -used both as a near-synonym for, or to refer to a sub-set of, science communication -that drew attention to the "lack of theory and knowledge base" and suggested that practitioners "can be characterised more as craftspeople operating through a model of apprenticeship, observation and audience approval" which the authors contrasted with the professional tradition of formalised mechanisms for recording knowledge and for training.…”
Section: The Ladder Of Professionalisationmentioning
confidence: 99%